2016
DOI: 10.1007/s00127-016-1250-3
|View full text |Cite
|
Sign up to set email alerts
|

Child abuse and the prevalence of suicide attempts among those reporting suicide ideation

Abstract: ObjectiveVictims of child abuse may be at increased risk of acting on suicide ideation, although this has not been empirically tested. We estimated the risk of suicide attempts associated with child abuse among individuals who reported suicide ideation.MethodsSecondary analysis of data from the population-based Canadian Community Health Survey Mental Health (n = 828). This population-based survey included various structured questionnaires, including the Composite International Diagnostic Interview to assess me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 35 publications
6
30
2
1
Order By: Relevance
“…Yet, unexpectedly, the role of coping on suicidality was only conveyed by positive coping-strategies but not additionally by negative coping-strategies, which were not significantly correlated with each other. This is in contrast to previous results ( 76 , 77 ) and might be caused by the fact that our CHR-patients rather reported a lack of positive coping-strategies than an excessive use of negative strategies. Furthermore, severe forms of trauma, such as sexual abuse that were predominately linked to an excessive use of negative coping-strategies were rare in our sample.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Yet, unexpectedly, the role of coping on suicidality was only conveyed by positive coping-strategies but not additionally by negative coping-strategies, which were not significantly correlated with each other. This is in contrast to previous results ( 76 , 77 ) and might be caused by the fact that our CHR-patients rather reported a lack of positive coping-strategies than an excessive use of negative strategies. Furthermore, severe forms of trauma, such as sexual abuse that were predominately linked to an excessive use of negative coping-strategies were rare in our sample.…”
Section: Discussioncontrasting
confidence: 99%
“…However, only perceptual abnormalities and attenuated hallucinations were significantly associated with suicidality. This specific association is in accordance with studies on psychotic-like experiences ( 29 , 77 ) and on patients with psychosis ( 93 ). However, no significant mediation effect of any attenuated psychotic symptom between childhood adversities as well as trauma and suicidality was found in this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…----------------------------------------------------------temperaments [16,17] or other personality traits [18], childhood trauma [19][20][21], and a family history of suicidal behavior [22][23][24].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Understanding and predicting suicidal thoughts, behaviours, and deaths has proven challenging given the complex aetiology beginning early in the life course [ 3 , 5 , 6 ]. There is a robust literature on suicide risk factors and research has identified a wide range of factors at the individual [ 3 , 7 10 ], family [ 11 13 ], and neighbourhood levels [ 14 16 ] to increased suicidality. However, much previous research have considered risk factors in isolation and predictive power for suicidal outcomes has been low despite over five decades of research attempting to better understand suicidality [ 17 ].…”
Section: Introductionmentioning
confidence: 99%